MODEL BANGKITAN PERJALANAN KOTA PALEMBANG MENGGUNAKAN RADIAL BASIS FUNCTION NEURAL NETWORKS - Arliansyah, Joni (Jurnal Transportasi, 2013)
Trip Generation Models in Palembang applying Radial Basis Function Neural Networks (RBFNN) is discussed in this paper. In this study, the data of trip production and land use are derived from the origin destination survey in Palembang in 2009, where the city of Palembang divided into 16 zones. To test the reliability of the model, the results of the RBFNN models are compared with the results of the regression analysis model. The results indicate that RBFNN model can give satisfactory prediction ability and it is better compare with the results of regression analysis where it can be seen from the coefficient of determination (R2) of the two models.Keywords: radial basis function neural networks, trip generation, land use, analisis regresi